Nursing education in Albania and global trends: Systematic review of clinical competence and health literacy - Dervishi, Alketa; Imami, Alma; Bezhani, Valbona; Kika, Etleva; Ivziku, Dhurata; Notarnicola, Ippolito; Zyberaj, Flora (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Nursing education is essential for preparing skilled health professionals capable of addressing public health challenges effectively. In Albania, aligning with international standards has brought significant changes to the nursing education system, yet challenges persist due to limited resources and the demand for diversified competencies. Comparing Albania's nursing education system with international experiences can provide valuable insights for enhancing its quality. This review examines the evolution of nursing education in Albania by comparing educational models and practices with international frameworks to identify strategies for improving nursing education in the Albanian context.Methods: A systematic review was conducted using major databases, covering the period from 2014 to 2024. Peer-reviewed studies in English and Albanian focusing on educational models, professional skills, and nursing education in Albania or globally were included. Study quality was assessed using the CASP criteria.Results: Seven studies were selected, highlighting critical aspects of nursing education, including health literacy, professional self-efficacy, clinical skills, guideline adoption, and e-learning programs. Findings indicate that effective nursing education should integrate health literacy to enhance patient communication, leverage online learning to address geographical disparities, and diversify clinical experiences to prepare nurses for complex healthcare environments.Conclusions: This review underscores the importance of evidence-based educational frameworks and standardized guidelines for advancing nursing education in Albania. The adoption of international strategies, such as incorporating health literacy and e-learning, can enhance educational outcomes, improve the quality of care, and foster a more resilient healthcare system capable of meeting population needs.